2021
DOI: 10.1177/23259671211016847
|View full text |Cite
|
Sign up to set email alerts
|

Application of Platelet-Rich Plasma in Arthroscopic Rotator Cuff Repair: A Systematic Review and Meta-analysis

Abstract: Background: It is unclear how and which factors affect the clinical efficacy of platelet-rich plasma (PRP) applied during arthroscopic rotator cuff repair. Purpose: To evaluate the clinical efficacy of PRP for arthroscopic repair of full-thickness rotator cuff tear and investigate the factors that affect its clinical efficacy. Study Design: Systematic review; Level of evidence, 1. Methods: We searched Cochrane Library, EMBASE, MEDLINE, and OVID to identify randomized controlled trials (RCTs) of patients who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…As a result, it cannot be proven that this improvement had an important effect on the pain, function, and activity levels of the patients. Similar results were reported by Xu et al in a recent meta-analysis [ 57 ], after a review of 14 randomized controlled studies. According to this study, the postoperative Constant–Murley score has had a statistically significant improvement for the PRP-treated patients with large or massive tears but was lower than the MCID, and the UCLA score improved significantly for this subgroup as well but was close to the estimated threshold for the MCID, while the ASES scores had no statistically significant difference between PRP-treated patients and control groups.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, it cannot be proven that this improvement had an important effect on the pain, function, and activity levels of the patients. Similar results were reported by Xu et al in a recent meta-analysis [ 57 ], after a review of 14 randomized controlled studies. According to this study, the postoperative Constant–Murley score has had a statistically significant improvement for the PRP-treated patients with large or massive tears but was lower than the MCID, and the UCLA score improved significantly for this subgroup as well but was close to the estimated threshold for the MCID, while the ASES scores had no statistically significant difference between PRP-treated patients and control groups.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have supported this hypothesis by demonstrating a correlation between the concentrated levels of growth factors, such as platelet-derived growth factor (PDGF) and transforming growth factor β1 (TGFβ1) and platelet counts [2][3][4][5]. To date, however, an increasing number of systematic reviews and meta-analyses have reported that the positive effects of PRP application are not only limited to tissue regeneration but also provide symptomatic relief in the treatment of several orthopedic indications, such as rotator cuff tears [6][7][8][9], chronic lumber pain, long bone fracture [10,11], knee osteoarthritis [12], lateral epicondylitis [13], and tendon and ligament [14]. However, a non-negligible number of review articles has expressed skepticism through their meta-analyses of similar orthopedic indications and suggested further randomized clinical trials with qualified PRP preparations in similar clinical indications [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…Many others followed these short-term studies with different results. A 2021 meta-analysis by Xu and Xue[ 23 ] reported that intraoperative PRP application significantly reduced retear rate and improved shoulder function only in large and massive rotator cuff tears. Two other meta-analyses conducted on randomized controlled trials published recently found that the addition of intraoperative PRP to both single-row and double-row repair improved functional results and retear rates.…”
Section: Introductionmentioning
confidence: 99%
“…Two other meta-analyses conducted on randomized controlled trials published recently found that the addition of intraoperative PRP to both single-row and double-row repair improved functional results and retear rates. [ 23 , 24 ] However, a recent study reporting the longest follow-up period with arthroscopic repair and PRP combination conducted by Randelli et al[ 25 ] in 2021 found no significant superiority of PRP at the end of a 10-year follow-up. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%